PENGARUH PHYSICAL EVIDENCE OBJEK WISATA PEMANDIAN AIR PANAS CIWALINI TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN (Survei pada Wisatawan Nusantara Pemandian Air Panas Ciwalini-Ciwidey Kabupaten Bandung) - Ananda, Rizka Putri; Ahman, Eeng; Ridwanudin, Oce (THE Journal : Tourism and Hospitality Essentials Journal, 2013)
Kabupaten Bandung is one of regions that has a lot of potential tourism object since it has many alternative destination for tourists to visit.One of the strenght of Bandung tourism are the enormous number of eco tourism objec ts that can be managed as best tourism area.Pemandian Air Panas Ciwalini is one out of 28 ecotourism destination that lays in Kabupaten Bandung.Every year the amount of visitors who visit pemandian Air Panas Ciwalini are fluctuated, which is seems to be decreased in the last two years.Based on the data, a research of effort on increasing the amount of visitor through management of physical evidence inside the site had been conducted.The aims of this research is to gain the result of examination about (1) Physical evidence which consist of facililty exterior, facility interior and other tangibles in the tourism object Pemandian Air Panas Ciwalini. (2) Visiting decisions which consist of choosing the tourism product, choosing the brand, choosing the travel agent, amount of visiting, and decision of visiting time of the tourist to Pemandian Air Panas Ciwalini. (3) The effect of physical evidence to the decision of the tourist on visiting Pemandian Air Panas Ciwalini.The object of this research is to acknowlegde the physical evidence which consist of facility exterior, facility interior and other tangibles on the the local tourist’s decisions to visit Pemandian Air Panas Ciwalini.The kind of research is descriptive and verivicative which use explanatory survey method.Population in this research was the domestic tourist from accros the country in Pemandian Air Panas Ciwalini.100 people had been taken to be the samples of the research which is using simple random sampling.Data analysis technique that is used in this research is Path Analysis MethodThe result on hipothesis examination showed that the physical evidence which consist sub variable such; exterior facilities,interior facilities and other tangibles, gives effects on visiting decisions to Pemandian Air Panas Ciwalini Interior facilities deliver the highest effects on taking the visit decision, whereas eksterior facilities give the lowest effects.